2021
DOI: 10.3389/fmicb.2021.717120
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Bacterial Community and Fermentation Quality in Leymus chinensis Silage Treated With Lactic Acid Bacteria and/or Water

Abstract: This study aimed to reveal the bacterial community and fermentation quality of Leymus chinensis silage during the fermentation process. L. chinensis was harvested at the heading stage, and ensiled with lactic acid bacteria (LAB, L), water (W), or a combination of both (LW) in vacuum-sealed plastic bags. As a control silage, untreated L. chinensis silage was also assessed. The samples were taken at 0, 5, 15, 35, and 60 days after ensiling. The bacterial community structure was assessed by plate cultivation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 39 publications
6
23
0
Order By: Relevance
“…Zhang et al (2018) showed that the addition of lactic acid bacteria and water promoted microbial succession during the early stages of fermentation. Xu et al (2021) showed that the addition of sodium benzoate and acetic acid improved quality and aerobic stability. There are few studies on the dynamics of quality, volatile chemicals and microorganisms in L. chinensis silage during aerobic exposure, and the relationship between them is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2018) showed that the addition of lactic acid bacteria and water promoted microbial succession during the early stages of fermentation. Xu et al (2021) showed that the addition of sodium benzoate and acetic acid improved quality and aerobic stability. There are few studies on the dynamics of quality, volatile chemicals and microorganisms in L. chinensis silage during aerobic exposure, and the relationship between them is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that there is a complex correlation network in the silage fermentation micro-ecosystem ( Bai J. et al, 2021 ; Du et al, 2021 ; Sun et al, 2021 ; Xu H. et al, 2021 ), while silage with high fermentation quality is characterized by a simplified bacterial-associated structure and aggregation of beneficial microorganisms ( Bai C. et al, 2021 ). The LAB inoculation treatment in this study simplifies the microbial correlation structure and promotes fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Its quality, palatability, and productivity were affected by the seasonal changes ( Kang et al, 2007 ), and it is difficult to provide high-quality L. chinensis year-round under grazing and haymaking systems ( Li et al, 2022 ). Ensiling is a satisfactory method for preserving L. chinensis to overcome the above shortcomings ( Pahlow et al, 2003 ; Xu et al, 2021 ). However, the insufficient epiphytic lactic acid bacteria (LAB) and the low moisture content (less than 600 g/kg) in materials negatively affect the fermentation process and the microbial dynamics and induce the Enterobacteriaceae succession in L. chinensis silage ( Xue et al, 2017 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ensiling is a satisfactory method for preserving L. chinensis to overcome the above shortcomings ( Pahlow et al, 2003 ; Xu et al, 2021 ). However, the insufficient epiphytic lactic acid bacteria (LAB) and the low moisture content (less than 600 g/kg) in materials negatively affect the fermentation process and the microbial dynamics and induce the Enterobacteriaceae succession in L. chinensis silage ( Xue et al, 2017 ; Xu et al, 2021 ). Previous studies reported that inoculating LAB at ensiling can improve the fermentation quality, aerobic stability, and digestibility of L. chinensis silage ( Tian et al, 2014 ; Zhang et al, 2015a ; Zhang and Yu, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation